The Effect of the Impact of Gross Domestic Product and Energy Consumption on Carbondioxide Emissions in Indonesia in the 1985-2019 Period - Putri Indah Lestari; Abdurrahman Shaleh; Syamsurijal A Kadir; Abdul Bashir (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
Economic growth in Indonesia will have its own impact, both positive and vice versa. One of the negative impacts arising from this economic growth is environmental damage such as an increase in the amount of carbon dioxide emissions. The Indonesian economy itself is very dependent on energy consumption, which is still largely dominated by fossil fuels. This study aims to determine the impact of the Gross Domestic Product (GDP) and energy consumption on carbon dioxide emissions in Indonesia in the period 1985-2019. The data used are secondary data with annual quantitative type. The method used is multiple linear regression Ordinary Least Square (OLS). The conclusion from the results of this study is that GDP and energy consumption have a positive and significant effect on the level of carbon dioxide emissions.